Pectate Lyase Genes Abundantly Expressed During the Infection Regulate Morphological Development of Colletotrichum camelliae and CcPEL16 Is Required for Full Virulence to Tea Plants - Hong Jiang; Qinghai Cao; Xinchao Wang; Wuyun Lv; Yuchun Wang (mSphere, 2023)
ABSTRACT Colletotrichum camelliae is the dominant species causing foliar diseases of tea plants (Camellia sinensis) in China. Transcriptome data and reverse transcription-quantitative PCR (qRT-PCR) analysis have demonstrated that the pectate lyase genes in C. camelliae (CcPELs) were significantly upregulated during infectious development on tea plants (cv. Longjing43). To further evaluate the biological functions of CcPELs, we established a polyethylene glycol (PEG)-mediated protoplast transformation system of C. camelliae and generated targeted deletion mutants of seven CcPELs. Phenotypic assays showed that the genes contribute to mycelial growth, conidiation, and appressorium development. The polypeptides encoded by each CcPEL gene contained a predicted N-terminal signal peptide, and a yeast invertase secretion assay suggested that each CcPEL protein could be secreted. Cell death-suppressive activity assays confirmed that all seven CcPELs did not suppress Bax-induced cell death in tobacco leaf cells. However, deletion of CcPEL16 significantly reduced necrotic lesions on tea leaves. Taken together, these results indicated that CcPELs play essential roles in regulating morphological development, and CcPEL16 is required for full virulence in C. camelliae. IMPORTANCE In this study, we first established a PEG-mediated protoplast transformation system of C. camelliae and used it to investigate the biological functions of seven pectate lyase genes (CcPELs) which were abundantly expressed during infection. The results provided insights into the contributions of pectate lyase to mycelial growth, conidial production, appressorium formation, and the pathogenicity of C. camelliae. We also confirmed the secretory function of CcPEL proteins and their role in suppressing Bax-induced cell death. Overall, this study provides an effective method for generating gene-deletion transformants in C. camelliae and broadens our understanding of pectate lyase in regulating morphological development and pathogenicity.